Nanostructured films from phthalocyanine and carbon nanotubes: Surface morphology and electrical characterization - Brito, Jackeline B.; Gomes, Douglas J. C.; Justina, Vanessa D.; Lima, Aline M. F.; Olivati, Clarissa A. [UNESP]; Silva, Josmary R.; de Souza, Nara C. (Academic Press Inc. Elsevier B.V., 2012)
We report on the investigation of the surface morphology and DC conductivity of nanostructured layer-by-layer (LbL) films from nickel tetrasulfonated phthalocyanine (NiTsPc) alternated with either multi-walled carbon nanotubes (MWNTs/NiTsPc) or multi-walled carbon nanotubes dispersed in chitosan (MWNTs + Ch/NiTsPc). We have explored the surface morphology of the films by using fractal concepts and dynamic scale laws. The MWNTs/NiTsPc LbL films were found to have a fractal dimension of ca. 2, indicating a quasi Euclidean surface. MWNTs + Ch/NiTsPc LbL films are described by the Lai-Das Sarma-Villain (LDV) model, which predicts the deposition of particles and their subsequent relaxation. An increase in the wetting contact angle of MWNTs + Ch/NiTsPc LbL films was observed, as compared with MWNTs/NiTsPc LbL films, which presented an increase in the fractal dimension of the first system. Room temperature conductivities were found be ca. 0.45 S/cm for MWNTs/NiTsPc and 1.35 S/cm for MWNTs + Ch/NiTsPc. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Multi-walled carbon nanotubes; Nickel tetrasulfonated phthalocyanine; Layer-by-layer (LbL) self-assembly films; Wetting contact angle; DC electrical conductivity; LDV model